Generational Wanderers: Seasonal Migrant Labor Through Three Generations - Heib, Lauren (The Toro Historical Review, 2024)
After the start World War, the United States found that manpower for agricultural work was limited, and thus began to outsource its seasonal labor to migrant farm workers. Despite the hardship of moving from place to place, and American citizen's prickly acceptance of migrant families, these laborers all over the country during harvest seasons, often leaving their homes for months at a time. Drawing from the oral history of Natividad “Nati” Castillo, his families migration around the United States during the spring and summer months became a generational pilgrimage. Ultimately three generations of Castillos would follow the same migration pattern with little variation. While Nati’s personal migratory experience ends just before the Agricultural Workers Movement lead by Cesar Chavez, Nati's oral history conceptualizes the migrants necessity of agricultural labor. Nati’s family, like many others, traveled on a seasonal, migrational track that moved out of the dry southern states, to northern states with plentiful crops waiting to be harvested.